2015
DOI: 10.1016/j.neurobiolaging.2015.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Influences of hormone replacement therapy on olfactory and cognitive function in postmenopausal women

Abstract: Olfactory dysfunction can be an early sign of Alzheimer’s disease (AD). Since hormone replacement therapy (HRT) may protect against developing AD in postmenopausal women, the question arises as to whether it also protects against olfactory dysfunction in such women. Three olfactory and 12 neurocognitive tests were administered to 432 healthy postmenopausal women with varied HRT histories. Serum levels of reproductive hormones were obtained for all subjects; APOE-ε4 haplotype was determined for 77. National Adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 45 publications
1
25
0
1
Order By: Relevance
“…It is known that women are greatly influenced by changes of female hormones, particularly during the menstrual cycle and menopause, and some women experience perceptual, cognitive and mental changes. In particular, for women in menopause, visual perception and the response to visual stimuli decline, and olfactory perception is likely to be decreased . Some studies about colour perception showed that female hormones could affect short‐wavelength light sensitivity, by which humans perceive bluish colour .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that women are greatly influenced by changes of female hormones, particularly during the menstrual cycle and menopause, and some women experience perceptual, cognitive and mental changes. In particular, for women in menopause, visual perception and the response to visual stimuli decline, and olfactory perception is likely to be decreased . Some studies about colour perception showed that female hormones could affect short‐wavelength light sensitivity, by which humans perceive bluish colour .…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Regarding perception, women are likely to have decreased abilities of visual perception, as shown by such indicators as declines of reaction time, [16][17][18] and also to have changes of olfactory senses, according to the hormonal changes in menopause. [19][20][21][22] However, some studies showed no strong associations between menopause and perceptual or cognitive functioning, 23,24 and menopausal symptoms can vary according to their individuals' health conditions and experiences. 13,25 Menopausal women may also have deficits in colour perception, particularly perception related to short-wavelength cones, 26 but the colour perceptual and cognitive functions affected by menopause have not been clearly identified.…”
Section: Perceptual and Cognitive Changes In Women In Menopausementioning
confidence: 99%
See 2 more Smart Citations
“…In this research field, the results were also contradictory. Whereas some studies provided evidence of a positive impact of HRT in postmenopausal women in various cognitive domains (for review see [30]) as well as olfactory sensitivity [31,32], there are also investigations that have shown a lack of significant differences in individuals using HRT [33]. Due to a huge increase in OC use within the last decades, numerous studies have been performed to investigate the influence of hormones in premenopausal women on various cognitive functions, such as verbal memory [34] or mental rotation [35].…”
Section: Discussionmentioning
confidence: 99%